Kajian Budaya Perkotaan Perspektif Lefebvrian Tentang Ruang Urban Kontemporer dan Seni sebagai Disalienasi - Benny Yohanes Timmerman (Jurnal Kajian Seni, 2022)
Cultural studies has developed into an intrinsically interdisciplinary research practice. The emergence of Urban Cultural Studies, as an extensive field of cultural studies, tries to clarify that the humanities-centered method of urban cultural studies requires a common ground that can unite social scientists and humanities scientists, in an effort to understand urban culture by focusing on its textual dimensions. Identifying urban problems as an interdisciplinary scientific work centered on urban areas, seeks to find ways to return intellectual specialization to the totality of understanding of “cultural texts”. This paper explores the formulation of urban cultural studies to bridge the discussion about the material condition and the cultural imagination of the city in a wider social context. The focus is on the analysis of Henri Lefebvre's thoughts on urban philosophy, urban modernity, and contemporary urban culture. Lefebvre reveals an awareness of the importance of space. Space in Lefebvre's understanding is the field of experience that is perceived, felt, and, most importantly, actually lived. Through Lefebvrian's perspective, this paper offers an understanding that the position of artwork, as one of the manifestations of urban culture, by overcoming disciplinary fragmentation can be seen as a disalienation strategy, becoming "living art" in the perspective of "work" as an effort to overcome product instrumentalization. This is also what the study of urban culture must realize; the totality of understanding of urban phenomena, or urban space as a reality and complexity of knowledge, cannot be understood in a compartmental way, which is only accepted as a collection of objects-economics, sociology, history, demography, psychology, or geology.